Promoting Stress Management and Wellbeing for Teachers, A Pilot Study - Hepburn, Stevie-Jae; Carroll, Annemaree; McCuaig, Louise (Frontiers in Education, 2021)
Objectives: Investigate the change in perceived stress, mindful attention awareness, subjective wellbeing and coping for pre-service teachers (PST) and the impact of a pilot 6-hour Complementary Intervention (CI). Method: Phase One (N = 79) survey at two timepoints. Perceived Stress Scale, Mindful Attention Awareness Scale, Personal Wellbeing Index and the Brief COPE scale. Phase Two CI pre- and post-program self-report measures (N = 20). Data analysis: Paired-sample and independent sample t-test. Results: The paired-samples t-test confirmed that perceived stress levels (p = .082) for PSTs remain elevated across the duration of the academic year. There was not a significant change for the MAAS and sub-scales of the Brief COPE. There was a significant decrease in PWI scores (p = .04). The participants in the CI experienced a significant decrease in perceived stress (p = .004) pre-program (M= 18.6, SD= 7.04) and post-program (M=15.55, SD = 6.95), effect size (d = .48). Increase in mindful attention awareness (p = 0.019), pre-program (M= 3.49, SD= 0.59) and post-program (M= 3.94, SD= 0.85), effect size (d = -0.57). Conclusion: The findings suggest that perceived stress for PSTs are at above average levels and a yoga-based CI may provide support for promoting wellbeing and stress management.